New type of hybrid nodal line semimetal in Be2Si - Z H Li; W Wang; P Zhou; Z S Ma; L Z Sun (New Journal of Physics, 2019)
Following Dirac and Weyl semimetals, nodal line semimetals represent a new type of topological semimetal and attracted extensive interest in modern condensed matter physics. Recently, a kind of hybrid nodal lines have been proposed (Zhang et al 2018 Phys. Rev. B 97 125143) and it mainly come from anisotropy interaction. Based on the first-principle calculations and k·p model, we predict a cubic Be _2 Si with topological nontrivial electronic states exhibiting fascinating type-I and type-II hybrid nodal line around Fermi level. Unexpectedly the low energy electronic states of Be _2 Si are isotropy in k _x and k _y directions and a new effective model has been proposed for the appearance of this new type hybrid nodal line. The four-fold degenerated type-I and type-II nodal points in the hybrid nodal lines along the high symmetry lines of Γ– K and Γ– X are protected by mirror reflection, time reversal and space inversion symmetry. The spin–orbit coupling effect only induces slight band gap in the hybrid nodal lines in Be _2 Si whose nontrivial nature remains. Moreover, the nontrivial hybrid nodal lines in Be _2 Si are robust to external strain. The results in present work indicate that Be _2 Si are promising candidates for future experimental studies of nontrivial topological semimetals and an excellent platform to study the interaction between the two types Dirac fermions.